Reference and information services : an introduction - Cassell, Kay Ann; Hiremath, Uma (Chicago : ALA Neal-Schuman, 2018)
"Guided by a national advisory board of educators and practitioners, this thoroughly updated text expertly keeps up with new technologies and practices while remaining grounded in the basics of reference work. Chapters on fundamental concepts, major reference sources, and special topics provide a solid foundation; the text also offers fresh insight on core issues, including ethics, readers' advisory, information literacy, selecting and evaluating reference materials, assessing and improving reference services, guidance on conducting reference interviews with a range of different library users, and much more"--
Introduction to reference and information services -- Determining the question : in-person, telephone, and virtual reference interviews -- Finding the answer : basic search techniques -- Answering questions about books, magazines, newspapers, libraries and publishing, and bibliographic networks : bibliographic resources -- Answering questions about anything and everything : encyclopedias -- Answering questions that require handy facts : ready reference sources -- Answering questions about words : dictionaries, concordances, and manuals -- Answering questions about events and issues, past and present : databases (and indexes) -- Answering questions about health, law, and business : special guidelines and sources -- Answering questions about geography, countries, and travel : atlases, gazetteers, maps, geographic information systems, and travel guides -- Answering questions about the lives of people : biographical information sources -- Answering questions about government and related issues : government information sources -- When and how to use the internet as a reference tool -- Readers' advisory services / Cindy Orr -- Reference services for children and young adults / Sujin Huggins -- Information literacy in the reference department -- Ethics in reference / Diana J. Floegel -- Selecting and evaluating reference materials -- Reference as programming -- Managing reference departments -- Assessing and improving reference services -- Reference 2.0 -- The future of information service.
Includes bibliographical references and indexes.
Keywords: Reference services (Libraries); Electronic reference services (Libraries); Reference books -- Bibliography; Electronic reference sources -- Directories